Performance of four-stage cascaded fiber optical parametric amplifier (FOPA) using optisystem - Mohamad Salleh, Fatin Nabilah (2017)
An optical fiber plays a significant role to cater the increasing transmission capacity. In optical fiber, there is a few nonlinear effects. One of the nonlinear effects is four-wave mixing (FWM). In-depth analysis of FWM is conducted and it is found that one of the applications in the FWM is a fiber optical parametric amplifier (FOPA). An FOPA has an ability to achieve a high gain and bandwidth. One of the approaches is a cascaded FOPA. A cascaded FOPA is a FOPA with two or more active media, commonly known as a highly nonlinear fiber (HNLF). Previous experimental work shows that the improvement in gain and bandwidth of the cascaded FOPA depends on the passive or active devices inserted in between the HNLF. However, the results at each stage of the cascaded FOPA are not discussed. The result at each stage is crucial to ensure that the cascaded FOPA is amplifying power at the respective stage which is the essence of this work. The cascaded FOPA is demonstrated by using an OptiSystem software with four stages of HNLF with different parameters. Two research work related to the cascaded FOPA are presented in this thesis. The first work focusses on the effects of pump dithering to the cascaded FOPA, while the second work discusses the effects of passive components to cascaded FOPA. The passive components selected are isolator and optical bandpass filter (OBPF). The results show that the FOPA with pump dithering can achieved the gain up to 27 dB, while without pump dithering, only 9 dB gain is achieved. For the performance of the cascaded FOPA with isolators, a high gain of 30 dB is obtained, while the cascaded FOPA with OBPFs, a wider bandwidth of 36 nm is obtained. In conclusion, the pump dithering and isolator can be used to achieved a high gain of FOPA and OBPF can be used to obtain a wider bandwidth of FOPA.